2014
DOI: 10.4103/0019-5413.144217
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive transforaminal lumbar interbody fusion

Abstract: Background:The use of minimally invasive surgical (MIS) techniques represents the most recent modification of methods used to achieve lumbar interbody fusion. The advantages of minimally invasive spinal instrumentation techniques are less soft tissue injury, reduced blood loss, less postoperative pain and shorter hospital stay while achieving clinical outcomes comparable with equivalent open procedure. The aim was to study the clinicoradiological outcome of minimally invasive transforaminal lumbar interbody fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…For patients with symptomatic lumbar spondylolisthesis, conventional TLIF has been accepted as one of the options for surgical management. 9 In past decades many published series have demonstrated similar clinical outcomes with MI-TLIF, which has caused less collateral tissue damage and blood loss, required a shorter hospital stay, and yielded an earlier recovery than conventional TLIF. 9,10,33 There was also the emerging option of dynamic stabilization in the management of low-grade spondylolisthesis with satisfactory results.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For patients with symptomatic lumbar spondylolisthesis, conventional TLIF has been accepted as one of the options for surgical management. 9 In past decades many published series have demonstrated similar clinical outcomes with MI-TLIF, which has caused less collateral tissue damage and blood loss, required a shorter hospital stay, and yielded an earlier recovery than conventional TLIF. 9,10,33 There was also the emerging option of dynamic stabilization in the management of low-grade spondylolisthesis with satisfactory results.…”
Section: Discussionmentioning
confidence: 92%
“…9 In past decades many published series have demonstrated similar clinical outcomes with MI-TLIF, which has caused less collateral tissue damage and blood loss, required a shorter hospital stay, and yielded an earlier recovery than conventional TLIF. 9,10,33 There was also the emerging option of dynamic stabilization in the management of low-grade spondylolisthesis with satisfactory results. The surgical approach of dynamic stabilization involves more soft tissue dissection than percutaneous pedicle screw insertion, but its biomechanical alterations remain elusive.…”
Section: Discussionmentioning
confidence: 92%
“…A number of series have demonstrated that MITLIF pro vided similar clinical and functional outcomes with less softtissue damage, decreased blood loss, reduced length of hospital stay, and earlier recovery than standard open TLIF. 11,12,28 In a retrospective study of 100 patients with lowgrade spondylolisthesis, there were no statistical dif ferences between 2 groups of patients who underwent open versus minimally invasive approaches with more than 4 years of followup. The clinical and radiological outcomes were similar, although longer operative time and more EBL were demonstrated in the group of patients who under went open TLIF.…”
Section: Discussionmentioning
confidence: 98%
“…11 During the last decade, MITLIF has been an emerging option. A number of series have demonstrated that MITLIF pro vided similar clinical and functional outcomes with less softtissue damage, decreased blood loss, reduced length of hospital stay, and earlier recovery than standard open TLIF.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few such reports from studies by Indian authors. Jhala et al, [16] prospectively studied 23 patients with MIS TLIF for degenerative spine disorders and demonstrated a good clinicoradiological outcome. Kandwal et al, [17] analyzed the usefulness of MIS TLIF in 23 cases of tuberculous spondylitis and found a good fusion rate with the use of the procedure.…”
Section: Discussionmentioning
confidence: 99%